The Role of Teachers in Increasing Literacy Interest in Students at SDN 1 Loloan - Karlina, Neta; Humaedah, Humaedah; Sumiadi, Raden; Azmiyati, Hasnani; Mariana, Mariana; Hanaria, Baiq Rika; Silpiani, Feni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of the research is to find out how teachers at SDN 1 Loloan contribute to increasing students' interest in literacy. This research is a subjective exploration with an investigative and contextual approach. The study was carried out by looking at various aspects of the teacher's role. Two class teachers at SDN 1 Loloan were used as research subjects. Location, SDN 1 Loloan teachers, and students were used as data sources. Direct observation, interviews, and documentation are data collection methods. The research results show that educators at SDN 1 Loloan play a role in developing interest in reading by creating, working on, generating, assessing and dynamizing comprehension exercises. Educators create new reading exercises related to the educational experience, provide office as a framework and administration for comprehension exercises, provide support to students, survey and assess the interactions and consequences of students' comprehension exercises, and make reading exercises economical.